The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1073/pnas.0812548106
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase ζ cooperates with polymerases κ and ι in translesion DNA synthesis across pyrimidine photodimers in cells from XPV patients

Abstract: Human cells tolerate UV-induced cyclobutane pyrimidine dimers (CPD) by translesion DNA synthesis (TLS), carried out by DNA polymerase , the POLH gene product. A deficiency in DNA polymerase due to germ-line mutations in POLH causes the hereditary disease xeroderma pigmentosum variant (XPV), which is characterized by sunlight sensitivity and extreme predisposition to sunlight-induced skin cancer. XPV cells are UV hypermutable due to the activity of mutagenic TLS across CPD, which explains the cancer predisposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(134 citation statements)
references
References 47 publications
8
125
1
Order By: Relevance
“…In keeping with our study, two-polymerase mechanisms, in which insertion by one (or more) specific TLS Pol(s) is followed by extension with another polymerase, has been suggested to play important roles in the replicative bypass of several other DNA lesions in mammalian cells. These included thymidine glycol, cis,syn-cyclobutane pyrimidine dimer, and pyrimidine(6 -4)pyrimidone photoproducts in mammalian cells (6,42,43,51,52). It would be interesting to unveil how different inserter and extender Pols as proposed here and in other studies (6,42,43,51,52) coordinate their actions during TLS across DNA damage in human cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with our study, two-polymerase mechanisms, in which insertion by one (or more) specific TLS Pol(s) is followed by extension with another polymerase, has been suggested to play important roles in the replicative bypass of several other DNA lesions in mammalian cells. These included thymidine glycol, cis,syn-cyclobutane pyrimidine dimer, and pyrimidine(6 -4)pyrimidone photoproducts in mammalian cells (6,42,43,51,52). It would be interesting to unveil how different inserter and extender Pols as proposed here and in other studies (6,42,43,51,52) coordinate their actions during TLS across DNA damage in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result may reflect a role for the residual Pol in TLS across S-cdG in cells. In this vein, it was suggested that residual TLS Pols might be sufficient for keeping the miscoding properties of some DNA lesions unchanged, even though sometimes lesion bypass efficiencies could be reduced by the siRNA knockdown of some specific TLS Pols (37,42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that three TLS polymerases (Poli, Polj and Polf) are involved in mutagenic TLS across CPDs and two of them (Polj and Polf) protect Polg-deficient cells against UV cytotoxicity (Yoon et al 2009;Ziv et al 2009). However, this alternative TLS pathway does not explain how stalled inactive Polg would be replaced by other TLS polymerase(s).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid model systems were instrumental in the study of DNA damage tolerance via TLS (e.g., refs. [21][22][23][24][25] and HDR (12,26); however, they do not obviate the need for studying TLS and HDR at the chromosomal level. To that end we developed a unique method, in which both TLS and HDR can be simultaneously analyzed at a single-nucleotide resolution in chromosomes of mammalian cells in culture.…”
mentioning
confidence: 99%